The Analysis of Basic Sentence Patterns in English Translation of the Holy Qur’an In Surah Ad Dukhan By Abdulloh Yousuf Ali - Arifah Wulandari (Register Journal, 2015)
This study is aimed at the analysis of basic sentence patterns in English translation of the holy Qur’an in surah Ad Dukhan. Focusing on the problem statements, there are two cases in this study. They are “What are types of the basic sentence patterns that is found in English translation of the Holy Qur’an in surah Ad Dukhan and what is the dominant of the basic sentence patterns types that is found in English translation of the holy Qur’an in surah Ad Dukhan. This research, applied descriptive qualitative method. The data is collected by documentation. The primary data is taken from surah Ad Dukhan in Abdullah Yousuf Ali’s English translation of the noble Al Qur’an. The secondary data is taken from many literary books and some relevant materials to support and complete the primary data source. The procedure of analyzing the data start by analyzing about basic sentence patterns types based on Nichols’s theory in his book English Syntax. Then find the dominant of the basic sentence patterns types of the holy Qur’an English by Abdullah Yusuf ‘Ali, in 1934 that is focus in surah Ad Dukhan. The overall findings showed that there were basic sentence patterns found in 52 cases are in sentence patterns 1consist of 12 cases, in sentence patterns 2 there are 19 cases, in sentence patterns 3 there are 7 cases, in sentence patterns 4 there are 10 cases, in sentence patterns 5 there are 4 cases. From the result the dominant cases that occurred of sentence patterns that found in Abdullah Yusuf Ali’s translation. The most dominant is sentence patterns 2. After analysis in this paper, the writer suggests in analyzing basic sentence pattern of English, we find that selection is an important syntactic process. The learner will get new idea doing observe as the writer done and they can possibly provide more book to have deeper analysis about that.